Sustained censorship in KZ (2022-01) (Kazakhstan) - Voidly (2022)
WARNING severity censorship detected in Kazakhstan. Confidence: 75%. Data sourced from OONI.
Censorship Incident ID: KZ-2022-0002
Keywords: censorship; KZ; censorship; warning